Multi-dressing and optical pumping effects in nonlinear gain from parametric-amplification four-wave mixing. (4th July 2018) - Cheng, Lin; Zhang, Da; Che, Junling; Ahmed, Irfan; Tang, Haijun; Zhang, Zhaoyang; Zhang, Yanpeng
Abstract: A higher degree of entanglement of entangled sources in quantum communications is always desired and can be achieved with high nonlinear gains. The dressing of atomic coherence and optical pumping can be considered as effective parameters to obtain such entangled sources. In this regard, we have experimentally studied doubly dressed effects in a small range of frequency, and optical pumping and de-pumping effects over a wide frequency range in multi-level atomic system in order to enhance the nonlinear gain. The multi-mode phenomenon that results from the multi-peak of Autler–Townes splitting can be observed at the large beam size of the pinhole of the pump field. Theoretical calculations fit well with the experimentally measured results. The dressing of atomic coherence and optical pumping lead to the enhancement of nonlinear gain up to 8.2 when the original nonlinear gain is 4.7.